Pilomatrixoma associated with anetoderma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
An 11-old-year boy presented a nodule on the right arm lasting 3 months and rapidly grown up to the current size of about 2 cm. On physical examination, there was a spheric, red-brownish nodule (Fig. 1), with regular surface and hard fibromatous consistency. A fibromatous nodule was clinically suspected. At palpation the nodule easily penetrated into the skin, that at its periphery presented a pleated, anetoderma appearance (Fig. 2). The nodule was removed under local anesthesia. Its histological examination showed the typical aspect of pilomatrixoma (Fig. 3). Verhoeff staining (Fig. 4) showed at the periphery of pilomatrixoma an almost complete absence of elastic fibers, leading to the final diagnosis of pilomatrixoma associated with anetoderma.